Numerical study of acoustic transmission across heavily damped plate using hybrid Ray-Tracing-SEA method. Issue 2 (June 2021) - Yan, Feng; Wilson, Robin; Rutherford, Peter
Energy transmission across lightly damped structures has been well studied including the approved success of statistical energy analysis in mid and high frequency bands. For heavily damped elements, the diffuse field theory, which is used in computing coupling loss factors, tends to fail. Energy attenuation with distance becomes more significant for such elements and hence the energy is less likely to be evenly distributed within those elements. A ray tracing algorithm is developed taking account of this phenomenon by tracking the travel history of a great number of discrete rays. The predicted transmitted energy is used in a modified statistical energy analysis model to calculate energy level difference between different subsystems. Numerical validation and comparison on a concrete five-plate system are conducted in both lightly damped and heavily damped cases. Both the classic and the hybrid models show good agreement for lightly damped system and differ for heavily damped system. The difference tends to become larger with increasing frequency and internal damping level. The parameter "effective length ratio" is proposed to describe the phenomena of energy concentration along the edge and as in indicator of whether the application of diffuse field theory is appropriate.